(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
Today, with the current state of our planet, we face the challenges to which old solutions will no longer be applicable. At the initiative of the United Nations with cooperation of the European Union, the Agenda 2030 for Sustainable Development was created. Although the idea of resource efficiency is known from previous periods, Agenda 2030 is characterized by its versatility. Regardless of differences in capacities and other circumstances, respecting the other singularities, the Agenda 2030 is suitable for the development of all countries at all levels of development. Achieving economic prosperity in the private sector with the support of the public sector, creating social innovation, on condition to adhere environmental rules, is the ideal solution for the future. Can we call such a model the business of the future ?